A Case Study of the Philadelphia Sugar-Sweetened Beverage Tax Policymaking Process: Implications for Policy Development and Advocacy. Issue 1 (January 2018) - Purtle, Jonathan; Langellier, Brent; Lê-Scherban, Félice
Abstract : Context: Policymakers are increasingly proposing sugar-sweetened beverage (SSB) taxes as an evidence-based strategy to reduce chronic disease risk; and local health departments (LHDs) are well-positioned to play a role in SSB policy development and advocacy. However, most SSB tax proposals fail to become law and limited empiric guidance exists to inform advocacy efforts. In June 2016, Philadelphia, Pennsylvania, passed an SSB tax. Objective: To identify features of the Philadelphia SSB tax policymaking process that contributed to the proposal's passage. Design: Qualitative case study. Semistructured interviews were conducted with key informants closely involved with the policymaking process. Interviews were audio-recorded and transcribed. Local news media about the SSB tax proposal were analyzed to triangulate interview findings. Analysis was conducted in NVivo 10 using inductive qualitative content analysis. Setting: Philadelphia, Pennsylvania, during the SSB tax policymaking in process. Participants: Nine key informants (2 city councilpersons, 4 city agency officials, 1 community-based advocate, 1 news reporter, and 1 researcher). Results: The Philadelphia SSB tax proposal was introduced with the explicit goal of financing universal prekindergarten and deliberately not framed as a health intervention. This framing shifted contentious debates about government involvement in individual behavior toward discussions about how to finance universal prekindergarten, a goal for which broad support existed. The LHD played an important role in communicating research evidence about potential health benefits of the SSB tax proposal at the end of the policymaking process. Conclusions: During local SSB tax policy development processes, LHD officials and other advocates should encourage policymakers to design SSB tax policies so that revenue is directed toward community investments for which broad public support exists. When communicating with policymakers and the public, LHDs should consider emphasizing how SSB tax revenue will be used in addition to presenting evidence about the potential health benefits of the SSB tax at the local level.